Dissolution Enhancement of Meloxicam Tablets from the Synergistic Effect of Hydrotropic and Sublimating Agent - Hemn L. Qader; Tara A. Abdula; Huner K. Omer (Polytechnic Journal)
Drugs which fall into Class II of Biopharmaceutical Classification System suffer from poor aqueous solubility that limits the dissolution and oral bioavailability. The improvement of the dissolution rate of this class of drug is an important issue for enhancing their bioavailability and therapeutic efficacy. The objective of this study is to investigate the magnitude of enhancement of the dissolution rate of Class II drug “Meloxicam (MLX)” by using more than one solubility enhancement technique.